2001
DOI: 10.1200/jco.2001.19.4.992
|View full text |Cite
|
Sign up to set email alerts
|

BAG-1: A Novel Biomarker Predicting Long-Term Survival in Early-Stage Breast Cancer

Abstract: These findings provide preliminary evidence that BAG-1 represents a potential marker of improved survival in early-stage breast cancer patients, independent of the status of axillary lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 41 publications
5
88
0
2
Order By: Relevance
“…Consistent with studies in other tumour types they found that approximately two thirds of tumours expressed high levels of BAG-1. In particular they found no correlations between BAG-1 and clinico-pathological parameters, but did find that, similar to the study of Turner et al (2001) in breast cancer, cytoplasmic expression of BAG-1 independently correlated with improved overall survival.…”
Section: Bag-1 and Other Malignanciesmentioning
confidence: 64%
See 4 more Smart Citations
“…Consistent with studies in other tumour types they found that approximately two thirds of tumours expressed high levels of BAG-1. In particular they found no correlations between BAG-1 and clinico-pathological parameters, but did find that, similar to the study of Turner et al (2001) in breast cancer, cytoplasmic expression of BAG-1 independently correlated with improved overall survival.…”
Section: Bag-1 and Other Malignanciesmentioning
confidence: 64%
“…By contrast, Turner et al (2001) reported no correlation between tumour grade and BAG-1 expression. Correlations with other clinical markers, such as oestrogen receptor alpha (ERa) and BCL-2 expression have been reported in various studies, but these appear to be not as strong as the correlation with grade and are more variably detected (Table 1).…”
Section: Bag-1 and Breast Cancermentioning
confidence: 88%
See 3 more Smart Citations